Fetomaternal outcome of eclamptic parturient in a tertiary care center: A descriptive cross-sectional study - Shrestha, Aashika; Shrestha, Junu; Gurung, Sangeeta; Adhikari, Anjali Subedi (Asian Journal of Medical Sciences, 2021)
Background: Eclampsia is still a leading cause of maternal death second to postpartum hemorrhage in developing countries. It is also associated with poor perinatal outcome. Aims and Objective: The objective of this study was to find the incidence, maternal and perinatal outcome of patients admitted in a tertiary hospital, Pokhara with diagnosis of eclampsia. Materials and Methods: A descriptive cross sectional study was conducted in department of obstetrics and gynecology, MTH, Pokhara for duration of 1 year from 1st January 2020 to 30th December 2020. A total of 22 patients were enrolled in the study irrespective of timing of occurrence of fits, age, parity, gestational age and status of booking on admission. Results: During the study period the incidence of eclampsia at our center was 0.85% .Majority of the patients 17(77.27%) were primigravida and 16(72.68%) delivered at less than 37 weeks of gestation. Only 4 patients had her antenatal checkup done in MTH. According to timing of occurrence of fits Antepartum and postpartum eclampsia comprise 50% each with no cases of intrapartum eclampsia. Caesarean section was done in 17(77%) cases. Among the cases 10, (45.45%) patients required ICU admission and 6(27.27%) required ventilator support. HELLP, acute renal failures, PRES, PPH were causes of maternal morbidity. Three (13.63%) babies were born stillbirth. Sixteen (72.72%) babies were born preterm and 13(59.09%) had birth weight less than 2.5kg. Six (27.27%) babies needed NICU admission. Conclusion: Eclampsia continues to be one of the prime etiological factors for maternal and perinatal morbidity and mortality in developing countries like ours. This is mostly due to the delay in seeking and reaching the care. Regular antenatal checkup, early recognition, its prevention and proper management of eclamptic cases are vital to tackle this challenge.